Loneliness and Suicidal Behavior: A Meta-Analysis - Dedara Hosiana Kandou; Firmanto Adi Nurcahyo (Buletin Psikologi)
Loneliness is an emotional condition that humans experience as social beings, which can be felt physically and psychologically. Loneliness can have a negative impact on mental health, e.g., causing a sense of isolation, stress, depression, and the development of suicidal tendencies. Several studies have shown variations in the correlation results between loneliness and suicidal behavior. This study aimed to analyze the correlation between loneliness and suicidal behavior across 19 studies (2015–2024) through a meta-analysis. This study used two artifacts, namely sampling and measurement errors. The results of the meta-analysis based on sampling error resulted in a correlation of 0.45, and a correlation of 0.51 was found when accounting for measurement error. The magnitude of the correlation indicates a moderate relationship. Positive correlation results suggest that loneliness can contribute to the emergence of suicidal behavior.